2017
DOI: 10.1113/ep086136
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 potentiates the ability of airway smooth muscle cells to promote angiogenesis by regulating VEGF signalling

Abstract: What is the central question of this study? Airway angiogenesis occurs in asthma, and airway smooth muscle (ASM) cells have been reported to be capable of promoting airway angiogenesis. What is the potential mechanism by which ASM cells harvested from patients with asthma are capable of promoting airway angiogenesis? What is the main finding and its importance? Endogenous STAT3 mediated the pro-angiogenic ability of ASM cells by directly activating VEGF signalling. These findings contribute to the understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The VEGF-VEGFR2 axis aids endothelial cell recruitment and vascular permeability, whereas ERK activates endothelial cell proliferation; FAK promotes cell migration and invasion. VEGF and VEGFR2 have been considered to be the most important factors in this pathway, and serve key roles in regulating angiogenesis via the modulation of the degradation, differentiation, proliferation and migration of vascular endothelial cells (3640). The VEGF-VEGFR axis eventually promotes the formation of new blood vessels (3639).…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF-VEGFR2 axis aids endothelial cell recruitment and vascular permeability, whereas ERK activates endothelial cell proliferation; FAK promotes cell migration and invasion. VEGF and VEGFR2 have been considered to be the most important factors in this pathway, and serve key roles in regulating angiogenesis via the modulation of the degradation, differentiation, proliferation and migration of vascular endothelial cells (3640). The VEGF-VEGFR axis eventually promotes the formation of new blood vessels (3639).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knockdown of STAT3 inhibits PDGF-induced ASM cell proliferation through the down-regulation of cyclin D3 and up-regulation of p27 expression [ 21 ]. A recent study reported that STAT3 promotes the pro-angiogenesis ability of ASM cells through up-regulation of vascular endothelial growth factor [ 37 ]. These studies suggest that STAT3 is a promising molecular target in preventing ASM cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT3 is found in peripheral blood mononuclear cells and airway smooth muscle tissues from asthma patients [9] and correlated with the increased cytokines [10]. Inhibition of STAT3 signaling can remit the airway inflammation [11], inhibit the proliferation of airway smooth muscle cells (ASMCs) and angiogenesis [9], and regulate IgE produce [12]. However, whether STAT3 signaling pathway could mediate the function of rhynchophylline on asthma remains unclear.…”
Section: Introductionmentioning
confidence: 99%